Ability of different methods to fill retrograde cavities with MTA - Roberta Bosso; Rodrigo Colturato Chagas; Arturo Aranda-Garcia; Ana Carolina Venção; Juliane Maria Guerreiro-Tanomaru1; Mario Tanomaru-Filho (Revista Sul-Brasileira de Odontologia, 2013)
The Mineral Trioxide Aggregate (MTA) has excellent biological property. However, its consistency makes it difficult to be inserted into retrograde cavities. Objective: To evaluate the ability of different methods to fill retrograde cavities with MTA. Material and methods: Root canals of thirty single-rooted resin teeth were prepared and filled. After the cut of 3 mm short of apical third, retrograde cavities with 3 mm deep were prepared using an ultrasound device and retrotips (CVD, São José dos Campos, SP, Brazil). The retrograde preparation was evaluate by using an operative microscope (D.F. Vasconcellos, São Paulo, SP, Brazil). The teeth were randomly divided into three groups (n = 10), according to the method: 1) condenser (Trinity, São Paulo, SP, Brazil); 2) MTA applicator (Angelus, Londrina, Brazil) + condenser; 3) condenser associated with ultrasound (CVD, São José dos Campos, SP, Brazil). After the filling of retrograde cavities with white MTA (Angelus, Londrina, Brazil), teeth were radiographed using a digital system (Kodak RVG 6000, Rochester, NY, USA). The images were analyzed by UTHSCSA Image Tool 3.0 software. The percentage of filling was calculated by the proportion between the total area of retrograde cavity and the filled area. The radiographic density mean of each third of retrograde cavity filled with MTA was measured by using the histogram tool of the software. The results were submitted to ANOVA and Tukey tests, with 5% of significance. Results: There was no difference in percentage of filling among the groups (p > 0.05) (approximately 85%). By comparing the thirds, the condenser and MTA applicator groups showed higher density for apical and middle third than cervical third (p < 0.05). The ultrasound group presented similar density among the thirds. Conclusion: The filling ability was similar for the studied methods. Ultrasound promoted better distribution of MTA in retrograde cavity, but did not increase the density of material.